The Mechanism of HLA-DM Induced Peptide Exchange in the MHC class II Antigen Presentation Pathway - Schulze, Monika-Sarah E. D. (2011)
HLA-DM serves a critical function in the loading and editing of peptides on MHC class II molecules. Recent data showed that the interaction cycle between MHC class II molecules and HLA-DM is dependent on the occupancy state of the peptide binding groove. Empty MHC class II molecules form stable complexes with HLA-DM, which are disrupted by binding of high-affinity peptide. Interestingly, MHC class II molecules with fully engaged peptides cannot interact with HLA-DM, and prior dissociation of the peptide N-terminus from the groove is required for HLA-DM binding. There are significant similarities to the peptide loading process for MHC class I molecules, even though it is executed by a distinct set of proteins in a different cellular compartment.